2012
DOI: 10.1186/1471-2377-12-64
|View full text |Cite
|
Sign up to set email alerts
|

Primary epidural lymphocyte-depleted Hodgkin’s lymphoma of the thoracic spine – presentation of a rare disease variant

Abstract: BackgroundLymphocyte-depleted Hodgkin’s lymphoma is the rarest form of classical Hodgkin’s lymphoma, accounting for < 1% of all cases. Patients often have advanced-stage disease at the time of presentation with an aggressive clinical course. Even more uncommon is primary extranodal disease and rarely it will be presenting with spinal cord compression.Case presentationAn 88-year-old Caucasian female presented with a history of upper back pain for several months and new onset bilateral leg numbness and weakness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…On the other hand, Peng et al reported that six of eight patients fully recovered after surgical decompression regarding their neurological impairment [26]. Others who have reviewed their patient data have come to similar conclusions [9,11,[27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, Peng et al reported that six of eight patients fully recovered after surgical decompression regarding their neurological impairment [26]. Others who have reviewed their patient data have come to similar conclusions [9,11,[27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 88%
“…1,2 Extra-nodal involvement of the disease is estimated at 10% of cases. [1][2][3][4][5] Epidural HL leading to a spinal cord compression occurs in 5% of cases, but usually at an advanced stage of the disease: it reveals the diagnosis in only 0.2% of cases. 4,6,7 Pathophysiology Epidural mass in HL may originate from hematogenous dissemination or more likely develops by direct spread from retroperitoneal or thoracic lymph nodes.…”
Section: Discussion Frequencymentioning
confidence: 99%
“…Hodgkin's disease usually presents with painless cervical adenopathy which may be accompanied by weight loss, long-term fever and night sweats. 2,3 Spinal cord involvement owing to an epidural mass is a rare complication that usually develops in the setting of a diffuse, undiagnosed disease or some time after the initial diagnosis. Then, the disease manifests itself with back pain and neurological deficits depending on the level and location of the lesion.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 2 more Smart Citations